If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(z + -6) = -4 Reorder the terms: 4(-6 + z) = -4 (-6 * 4 + z * 4) = -4 (-24 + 4z) = -4 Solving -24 + 4z = -4 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 4z = -4 + 24 Combine like terms: -24 + 24 = 0 0 + 4z = -4 + 24 4z = -4 + 24 Combine like terms: -4 + 24 = 20 4z = 20 Divide each side by '4'. z = 5 Simplifying z = 5
| 3y=51x | | 51x=3y | | 15-4x=-5x-9 | | 9h+7=88 | | 2(2x-7)=-2 | | 3(2x-5)(4x+31)=0 | | 49x+90=4x+45 | | 3x+21=x+51 | | 0.1u-3.3=-1.4u+5.8 | | 450000=0.15x | | 2a-9= | | 7-21x/15x-5 | | 2x+150=5x+121 | | y=6/10x | | 23y-y^2=76 | | 2x+150=5x+151 | | 7-4x+2=2x+3 | | 8m-21=35 | | 3e^2x-7=50 | | 4x+18=2x+36 | | 3e=50 | | -9+8k-3-6k= | | 81x=5y | | 4x+18=2x+34 | | 6y-11y=-28-37 | | (t-3)(t-4)=0 | | 3(x+2)-4(2-x)=-2+7x | | k^2+8=-2k | | 8x+72=2x+24 | | 3a^2-8a=-4 | | 5x+41-6x=2-7x+3 | | 5xy-xy+2x-y= |